TEACHERS’ PROFESSIONAL KNOWLEDGE APPLICATION PRACTICES AND STUDENTS’ ACADEMIC PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN KAKAMEGA NORTH SUB-COUNTY, KENYA - Chimuche, Simon Kangwana; Kikechi , Ronald Werunga; Ngome , Charles Kibanani (IJRDO - Journal of Social Science and Humanities Research, 2023)
The purpose of this study was to assess the effect of teachers’ professional knowledge application practices on students’ academic performance in public secondary schools in Kakamega North sub-county, Kenya. The study was guided by the Goal setting theory. A descriptive survey research design was utilized. The target population was 772 persons comprising of 723 teachers, 49 principals, and 49 deputy principals from Kakamega North’s public secondary schools. A sample size of 232 was obtained using Krejcie and Morgan’s Table for determining sample sizes. The researcher then applied proportionate sampling approach to determine the number of respondents in each group. Thus, 217 teachers, 15 principals, and 15 deputy principals were used as respondents. Questionnaires, interview schedules, and document analysis were utilized in data collection. The reliability coefficient of the instruments was determined using the test-retest technique with Cronbach’s alpha statistic being used to calculate its reliability. A reliability value of 0.842 was established which was considered sufficient to get consistent outcomes. The validity of the instruments was determined by the experts in the area of specialization. Data was analyzed using descriptive statistics and Chi-Square analysis. The qualitative data was processed and presented using quotations according to the study’s topics and sub themes. The study established that there is no statistically significant relationship between teacher professional knowledge application appraisal practices and students’ academic performance in public secondary schools in Kakamega North Sub-county, Kenya. The study recommends that a policy is needed to strengthen these variables in order to realize better academic results from students in public secondary schools. The study is hoped to benefit the education stake holders, policy makers and community members in improving the students’ academic performance.